Assessment in English Language Teaching: Assessment in Practice - Hadi , Muhammad Zaki Pahrul (Jurnal Ilmu Sosial dan Humaniora, 2023)
The terms of test, assessment, examination, and evaluation are sometimes difficult to differentiate. The purpose of this interview is to measure teachers understand the terms of test, assessment, examination, and evaluation. As educators, actively involved in evaluation practices, we would argue that assessment has an important influence on students’ learning. In this study, the researcher tried to find the data from the interview with the English teachers. The interview also tried to find out the difficulties faced by teachers in organizing (preparing, administering, marking, and interpreting) the test. The English teachers teaching at SMK Pelayaran Semarang, based on their requests, so their names are in this article are replaced with relevant codes, Mrs. A and Mr.B. From the findings, the researcher can conclude that the teacher had tried to make the test valid and reliable for the students. Based on the principles, the teacher also tried to implement wash-back principles by giving feedback to the students. Moreover, the teachers also need to know the brief distinction between test, assessment, examination, and evaluation.